Determinan Penghindaran Pajak: Moderasi Keterbatasan Keuangan - Nia Rifvany Agustin Wulandari; Nadya Fitriyah Nur Aisyah; Fitra Ria Silvida; Rony Wardhana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: This study aims to examine the effect of corporate risk, capital intensity ratio, and family ownership on tax avoidance, by considering financial constraints as a moderating variable. Method: This study uses data of 225 observations from the cen sus technique where all LQ45 companies on the Indonesia Stock Exchange are the research sample. The data were analyzed using the Partial Least Square (PLS) approach with the help of SmartPLS software. Results: The results show that corporate risk and family ownership have a positive and significant effect on tax avoidance. The capital intensity ratio does not show a significant effect. Financial constraints significantly moderate the relationship between family ownership and tax avoidance in a negative direction. Implication: This study enriches tax avoidance literature by highlighting the role of ownership structure and internal financial conditions, offering valuable insights for tax policy and fiscal oversight. Novelty: The study introduces financial constraints as a moderator in the link between family ownership and tax avoidance—an underexplored area in Indonesian public companies—using LQ45 firms to reflect real market dynamics.